The Rôle of Lobby Believers in Determining Policy Administration and Thread Colonialism in Algèria - BEKKAR, Mohamed; BOUKERROUBA, Mohamed (Journal of Human Sciences, 2020)
Algéria has seen European delegates since 1830, but they controlled the contry and controlled its budget after 1900. They rejected the 1919 reforms, visited the élections stood up to the Algérian National Movement and the aspirations of the Algérians,and pressed the French Colonial Administration and the French autority in Paris. The stood behind the May 8,1945 massacres,and fought the libération révolution in1954 to presserve Algéria-French.